Autonomia da práxis docente na universidade: condições e possibilidades - Freire, José Carlos da Silveira (2013)
This work integrates research line Fundamentals of Educational Processes, of the Postgraduate Program in School of Education, Federal University of Goiás. Its objective was to apprehend the conditions and possibilities of the autonomy of teaching praxis developed at the university. From a critical questioning of subjective autonomy conception in Rousseau and Kant, and intersubjective in Hegel, anchored in the theoretical and methodological framework of historical and dialectical materialism which discusses autonomy as human emancipation, this work revealed the sense of autonomy manifested in teaching practice developed in a public university. As theoretical contributions of Marx, Adorno and Horkheimer are references, the concept of autonomy is apprehended as praxis socio- historical and cultural criticism praxis, in the midst of other conceptions of teaching autonomy in dispute in the public university. The empirical study sought to demonstrate autonomy conceptions of teachers of a Pedagogy Course at a public university and of assessment that these teachers do of conditions and possibilities of autonomy in teaching. The informations on autonomy conceptions were collected through a questionnaire and interviews with eight of the 25 PhD teachers of the effective staff of Pedagogy Course of UFT with labor regime "exclusive devotion" and with more than three years of professional practice. The analysis has revealed that, among the conceptions of teaching autonomy, there is a predominance of conceptions of autonomy, as moral and intellectual praxis, expressed in the idea of "individual responsibility" and "possession and control of scientific knowledge". The conditions and possibilities of autonomy as praxis which aim emancipation are given by configuration of teaching working in contemporary, which paradoxically requires greater skill and subjective involvement in the work process, while this becomes precarious and intensified, producing situations of conformism and resistance to domination and capitalist exploitation. The pursuit and achievement of better teaching work conditions suggest a relative independence of thinking and doing investigative and teaching work at the university, while the processes of bureaucratization compress innovation and creativity, and difficult teaching to be experienced as emancipatory praxis which calls into question the mode of organization and operation of the university and society as a whole.